THE APPLICATION OF LEAN SUPPLY CHAIN IN THE PROCESS OF LOADING AND UNLOADING FISH IN UKM CAMAR LAUT SOUTH JAKARTA - Syarifuddin Nasution; Ainul Haq; Siska Karmilah (Asosiasi Dosen Muda Indonesia, 2024)
Lean supply chain is an approach used by various parties that are interconnected to achieve targets in the supply chain, useful to continuously increase customer satisfaction and to reduce processes that have no added value. Problems that occur in the process of loading and unloading fish in UKM Camar Laut South Jakarta are still a lot of waste, including the uncertainty of product delivery time, the number of excess transportation activities and the existence of defects in the product. These problems can be solved using a lean supply chain approach with Waste Assessment Model tools. The purpose is to identify the highest type of waste, determine the value added (VA); non value added (NVA); necessary non value added (NNVA) by using VALSAT tools selected and provide improvement suggestions. The highest type of waste that occurs is a defect of 20,278%. Based on the selected VALSAT tools namely process activity mapping tools, VA is 63.888%; NVA is 25,606%; NNVA is 10.512%. Proposed improvements in the process of loading and unloading fish are unnecessary process removals, warehouse integration, improvements to UKM management. Based on the creation of future state value stream mapping, there was an increase in the percentage value of value added by 8.078%, a decrease in the percentage of non value added value of 9.222% and an increase in the percentage of the value of necessary non value added of 1.143%.